Domestic abuse and the provision of advocacy services: mapping support for victims in family proceedings in England and Wales. Issue 3 (3rd July 2022) - Speed, Ana
ABSTRACT: The role that domestic abuse services play in supporting victims through the family courts is under documented in domestic abuse literature, save for a recent enquiry conducted by SafeLives which was published in June 2021. The key contribution of that report was in providing quantitative insights into the extent of support available for victims in family court proceedings. This article seeks to build on the work of SafeLives by presenting empirical insights from a separate study in which 29 domestic abuse specialists and legal professionals either completed an online questionnaire, participated in a semi-structured interview, or engaged in both forms of participation. Whilst there is some overlap in the remit of this study and the SafeLives' study, there are also important methodological differences which impact upon the respective findings, not least that this study has a greater qualitative focus and therefore provides richer insights. The conclusions are timely in light of the Home Office announcement that £81 million is being made available to recruit 700 Independent Domestic and/or Sexual Violence Advisers, and the introduction of Domestic Abuse Protection Orders under the Domestic Abuse Act 2021, which may see non-legally qualified specialists take a greater role in securing family court protection.